Prediction of Bankruptcy in Islamic Banking in Indonesia: Modified Altman Z-Score Method Approach - Surepno Surepno; Er Melinda Swissa (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstract Islamic banking as an entity requires an annual financial performance evaluation to ensure the health and sustainability of the company. This study aims to assess the level of soundness and bankruptcy prediction of Islamic banking using the modified Altman Z-Score analysis method. This study uses a quantitative approach. The sample used is 12 Islamic Commercial Banks in Indonesia. The data used to measure the health and bankruptcy of banks is the financial statements of Islamic commercial banks for the 2017-2019 period. The results show that the health level of 11 Islamic commercial banks is in a safe area position or it can be said that the company is in a healthy condition (not bankrupt) during the 2017-2019 period and 1 Islamic commercial bank, namely Panin Dubai Syariah Bank, is in a cautious position (gray area). ). This is because the 11 Islamic commercial banks have a Z-Score 2.6 and 1 Islamic bank has a Z-Score 1.10 Z2.6.